Exploring the Intersection of Christian Theology and Ikigai: Implications for Vocational Ministry and Faith Formation - Pantan, Frans (BIA': Jurnal Teologi dan Pendidikan Kristen Kontekstual, 2024)
Integrating the concept of Ikigai from the Japanese tradition with Christian theology in the context of vocational ministry and faith formation emphasizes the balance between passion, profession, mission, and vocation. Ikigai strengthens the internalization of Christian values in everyday life, especially in work and ministry. In the era of globalization and secularization, the fragmentation of values is a challenge that makes it difficult for many Christians to align their spiritual calling with the demands of modern and professional life. Ikigai offers a holistic approach that unites spiritual and worldly aspects, giving new meaning to work to fulfill the divine calling. By applying Ikigai in Christian religious education, individuals can find a balance between work, faith, and service to others. This helps people live a more meaningful life calling and strengthens their commitment to the faith and mission that God has set so that professional and spiritual lives support each other.